2010
DOI: 10.1016/j.parint.2010.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Helminth communities of loggerhead turtles (Caretta caretta) from Central and Western Mediterranean Sea: The importance of host's ontogeny

Abstract: We investigated the factors providing structure to the helminth communities of 182 loggerhead sea turtles, Caretta caretta, collected in 6 localities from Central and Western Mediterranean. Fifteen helminth taxa (10 digeneans, 4 nematodes and 1 acanthocephalan) were identified, of which 12 were specialist to marine turtles; very low numbers of immature individuals of 3 species typical from fish or cetaceans were also found. These observations confirm the hypothesis that phylogenetic factors restrict community … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 34 publications
2
51
1
Order By: Relevance
“…The turtle in this study had ingested mainly algae that is unusual for this species and would indicate inability to forage effectively in its environment. It might explain the rich helminth fauna here found since sea turtles with vegetarian diet would ingest accidentally and more easily great amount of mollusk intermediate hosts whose live on marine pasture with respect to turtles with mainly spongivorous or carnivorous habits (Pérez Ponce de León et al, 1996;Santoro et al, 2006Santoro et al, , 2010Santoro & Mattiucci, 2009). Infection by spirorchiid flukes represents the main parasitological health problem of sea turtles.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The turtle in this study had ingested mainly algae that is unusual for this species and would indicate inability to forage effectively in its environment. It might explain the rich helminth fauna here found since sea turtles with vegetarian diet would ingest accidentally and more easily great amount of mollusk intermediate hosts whose live on marine pasture with respect to turtles with mainly spongivorous or carnivorous habits (Pérez Ponce de León et al, 1996;Santoro et al, 2006Santoro et al, , 2010Santoro & Mattiucci, 2009). Infection by spirorchiid flukes represents the main parasitological health problem of sea turtles.…”
Section: Discussionmentioning
confidence: 87%
“…Studies on sea turtles suggest that ontogenetic and ecological factors influence strongly their helminth communities (Pérez Ponce de León et al, 1996;Santoro et al, 2006Santoro et al, , 2010. Unfortunately, no information exists on helminth community of hawksbill turtle at both hierarchical levels of organization (the component community and infracommunity), and the known data is fragmented and based on occasional findings of stranded individuals (Oguro, 1936;Chattopadhyaya, 1972;Fischthal & Acholonu, 1976;Dyer et al, 1995;Werneck et al, 2008;Greiner, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…2F). Previous records: In C. caretta from Egypt (Braun, 1901;Looss, 1899); France (Euzet & Combes, 1962); Italy (Manfredi et al, 1998); Mediterranean (Aznar et al, 1998;Santoro et al, 2010); Madera (Valente et al, 2009), Adriatic sea (Gracan et al, 2012) and USA (Greiner, 2013); C. mydas from Egypt (Looss, 1902), USA (Greiner, 2013) and Brazil (Present report); E. imbricata from Cuba (Groschaft et al, 1977); L. olivacea from Mexico (Pérez-Ponce de León et al, 1996;Vivaldo et al, 2006) and Costa Rica (Santoro & Morales, 2007) and L. kempii from and USA (Greiner, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…microvitellatus Chattopadhyaya, 1970; E. schikhobalovae Gupta & Mehrotra 1976 and E. carettae Blair & Limpus 1982. Although these parasites are carried out at various locations in the world, on different hosts (Santoro et al, 2010), None of these species have previously been reported in hosts found in the SouthWest Atlantic Ocean (Fernandes & Kohn, 2014). The aim of this note is report the fi rst occurrence of E. megachondrus in a juvenile Chelonia mydas Linnaeus, 1758 from Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…During spring migrations of 2014 and 2015, we identified and enumerated intestinal helminths in 130 scaup from stopover locations in four regions of the upper Midwest, to examine the effects of host age and body size as well as the region and year of collection on helminth infracommunity structure (Santoro et al, 2010(Santoro et al, , 2012Kanarek & Zaleśney, 2013). Results from this investigation will be valuable for identifying possible relationships between intestinal helminth communities and key stopover locations of spring-migrating scaup.…”
Section: Introductionmentioning
confidence: 99%